2016
DOI: 10.1089/met.2015.0065
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Subclinical Hypothyroidism and Metabolic Syndrome as Defined by the ATP III Criteria

Abstract: The association between subclinical hypothyroidism (SCH) and metabolic syndrome (MetS) is a matter of debate. In this study, we aimed to examine the risk of MetS in SCH through a systematic review and meta-analysis. A systematic search of published literature up to September 2015 was conducted. General population studies were included if they had considered SCH as the independent variable. After data extraction, a meta-analysis was run to assess the odds ratio (OR) of MetS and its components between subclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…Observational studies concerning the association between SCH and MetS have shown contradictory results. In addition, two recent meta-analyses also failed to clarify this problem; one of them found a positive association [27], whereas no association was found in the other study [28]. CVD risk and mortality are increased in SCH [4, 5], particularly among subjects younger than 65 years and in those with a TSH concentration greater than or equal to 10 mIU/L.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies concerning the association between SCH and MetS have shown contradictory results. In addition, two recent meta-analyses also failed to clarify this problem; one of them found a positive association [27], whereas no association was found in the other study [28]. CVD risk and mortality are increased in SCH [4, 5], particularly among subjects younger than 65 years and in those with a TSH concentration greater than or equal to 10 mIU/L.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis assessed the association between metabolic syndrome and SHypo by employing the Adult Treatment Panel III (ATP III) criteria for MetS. (341) Although this study did not report a significant difference in MetS prevalence between SHypo and euthyroid individuals (OR = 1.13, 95% CI 0.95-1.34), the prevalence of central obesity (OR = 1.43, 95% CI 1.04-1.96) was significantly higher in the SHypo group, and hypertriglyceridemia was prevalent in the female group with SHypo (341). There are reports on higher TSH levels in metabolic syndrome patients than in healthy ones, and high prevalence of metabolic syndrome in subjects with TSH level higher than normal when compared to those with normal TSH levels (177,342).…”
Section: Association Between Metabolic Syndrome and Thyroid Hormonmentioning
confidence: 99%
“…Two MAs34 35 have confirmed that SCH was not associated with MetS, and the AMSTAR scores were high. Three MAs29 45 47 have investigated the effect of SCH on cognitive function and shown that SCH was not significantly associated with cognitive impairment.…”
Section: Discussionmentioning
confidence: 93%
“…Among the 52 included eligible MAs, 4628–73 (46/52, 88.5%) were published in English, and the rest74–79 (6/52, 11.5%) were published in Chinese. The 52 included MAs contained 685 studies, with an average of 13.2 (range: 3–39) studies per article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation